Wireless Secure Communication Based on Code Domain Space-Time Modulated Metasurface - Xinyu Fang; Xuezhi Zheng; Mengmeng Li; Zhiyu Li; Dazhi Ding (Electromagnetic Science)
The emergence of space-time modulated metasurface (STMM) as a novel platform for signal modulation holds significant promise for wireless secure communication, particularly within modern information technologies such as Internet of things and the 5th generation and beyond. While previous secure communication methods based on STMM have primarily focused on ensuring information security within both the time and frequency domains, in this study, we introduce a novel code domain modulation scheme in STMM to facilitate wireless secure communications, which is difficult to be detected in both time and frequency domains. The core concept involves synthesizing a smart modulation waveform by using a new code domain so that both secure information transmission and mitigation of jamming are realized. To achieve this, we build a Q-dimensional signal space that has a minimum overlap with the jamming signal space and where orthogonal or quasi-orthogonal basis functions are used for information transmission. Furthermore, this methodology can be readily extended to other abstract signal domains. To exemplify this approach, we implement an STMM and utilize it to transmit the logos of our universities accurately, while eavesdroppers are unable to acquire any useful information through direct identification from the constellation diagrams. This showcases the effectiveness of the proposed secure communication system.